1999
DOI: 10.1111/j.1469-7793.1999.0035o.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of α2‐δ and other accessory subunits on expression and properties of the calcium channel α1G

Abstract: Voltage-dependent calcium channels and currents in native neurons and other cells have been divided into high voltage activated (HVA) and low voltage activated (LVA) (Carbone & Lux, 1984;Nowycky et al. 1985). LVA currents can be distinguished by their activation at smaller depolarizations, near to the resting potential, and by their rapid inactivation (Huguenard, 1996). At the single channel level, channels with a small unitary conductance activate over the same voltage range (Carbone & Lux, 1984). Native T-ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
3

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 40 publications
6
81
0
3
Order By: Relevance
“…Similarly, coexpression of cloned ␤-subunits has little or no effect on cloned T-type channel activity (100). In contrast, coexpression with either ␣ 2 ␦ 1 or ␣ 2 ␦ 2 was found to double the size of Ca v 3.1-mediated currents (100,132). Concomitant immunolocalization studies supported the contention that this rise in currents was due to increased expression of ␣ 1 -␣ 2 ␦ 1 complexes at the plasma membrane (100).…”
Section: E Auxiliary Subunits?supporting
confidence: 60%
See 1 more Smart Citation
“…Similarly, coexpression of cloned ␤-subunits has little or no effect on cloned T-type channel activity (100). In contrast, coexpression with either ␣ 2 ␦ 1 or ␣ 2 ␦ 2 was found to double the size of Ca v 3.1-mediated currents (100,132). Concomitant immunolocalization studies supported the contention that this rise in currents was due to increased expression of ␣ 1 -␣ 2 ␦ 1 complexes at the plasma membrane (100).…”
Section: E Auxiliary Subunits?supporting
confidence: 60%
“…Antisense depletion of ␤-subunits causes profound reductions in HVA channel density; however, this treatment has no effect on T-type channels recorded from the same neurons (226,234). Similarly, coexpression of cloned ␤-subunits has little or no effect on cloned T-type channel activity (100). In contrast, coexpression with either ␣ 2 ␦ 1 or ␣ 2 ␦ 2 was found to double the size of Ca v 3.1-mediated currents (100,132).…”
Section: E Auxiliary Subunits?mentioning
confidence: 80%
“…It is also supported by the lack of biochemical evidence for direct interactions between wild-type ␣1G and other poreforming or regulatory Ca 2ϩ channel subunits, except for the finding that functional expression of ␣1G increases with coexpression of ␣2␦ and ␤1b subunits (Dolphin et al, 1999). These data demonstrate that mutations of Ca 2ϩ channel subunit genes are not required to induce the elevated LVA Ca 2ϩ currents in thalamic neurons that are associated with SWDs.…”
Section: Thalamic Casupporting
confidence: 49%
“…Previous in vitro studies have shown that ␣2␦-1, ␣2␦-2, and ␣2␦-3 subunits act to increase the maximum conductance of a number of expressed calcium channel ␣ 1 /␤ subunit combinations at the whole cell level (2,(43)(44)(45)(46). However, this may be dependent to some extent on the specific combination of ␣ 1 and ␤ subunits expressed.…”
Section: Discussionmentioning
confidence: 65%